Borax-based gel electrophoresis: A novel approach for RNA integrity analysis - Abdulhadi Albaser (PLoS ONE, 2026)
This study investigates the unexpected utility of borax-based agarose gel electrophoresis for RNA integrity assessment. Accurate RNA integrity analysis fundamentally requires denaturation to fully resolve RNA molecules from their complex secondary structures and prevent aggregation, a principle typically achieved with hazardous chemicals like formaldehyde. Through multiple independent experiments, this work demonstrates that borax, beyond its buffering properties, exhibits denaturing-like behavior, effectively separating RNA molecules with resolution comparable to formaldehyde-based methods. This finding is surprising and challenges conventional understanding. To validate the method's versatility, it was successfully applied to total RNA extracted from six diverse microbial species, including Gram-negative bacteria ( E. coli , Pseudomonas aeruginosa ), Gram-positive bacteria ( Staphylococcus aureus , Enterococcus faecalis ), and eukaryotic fungi ( Candida glabrata , Candida albicans ). This novel method offers a compelling and safer alternative to traditional formaldehyde-based approaches for RNA analysis in various research and clinical settings. It provides several advantages, including enhanced safety, simplified protocols, and reduced electrophoresis time. By eliminating the need for pre-treatment steps and utilizing borax as both a buffer and an apparent denaturant, this method significantly streamlines RNA analysis. While the precise mechanism underlying this denaturing-like effect requires further elucidation, this study highlights a promising, accessible, and universally applicable tool for robust RNA integrity assessment.